N-Terminal Pro-B-type Natriuretic Peptide Is Useful to Predict Cardiac Complications Following Lung Resection Surgery - Lee, Chang Young (Korean Society for Thoracic and Cardiovascular Surgery, 2011)
BACKGROUND: Cardiovascular complications are major causes of morbidity and mortality following non-cardiac thoracic operations. Recent studies have demonstrated that elevation of N-Terminal Pro-B-type natriuretic peptide (NT-proBNP) levels can predict cardiac complications following non-cardiac major surgery as well as cardiac surgery. However, there is little information on the correlation between lung resection surgery and NT-proBNP levels. We evaluated the role of NT-proBNP as a potential marker for the risk stratification of cardiac complications following lung resection surgery. MATERIAL AND METHODS: Prospectively collected data of 98 patients, who underwent elective lung resection from August 2007 to February 2008, were analyzed. Postoperative adverse cardiac events were categorized as myocardial injury, ECG evidence of ischemia or arrhythmia, heart failure, or cardiac death. RESULTS: Postoperative cardiac complications were documented in 9 patients (9/98, 9.2%): Atrial fibrillation in 3, ECG-evidenced ischemia in 2 and heart failure in 4. Preoperative median NT-proBNP levels was significantly higher in patients who developed postoperative cardiac complications than in the rest (200.2 ng/L versus 45.0 ng/L, p=0.009). NT-proBNP levels predicted adverse cardiac events with an area under the receiver operating characteristic curve of 0.76 [95% confidence interval (CI) 0.545~0.988, p=0.01]. A preoperative NT-proBNP value of 160 ng/L was found to be the best cut-off value for detecting postoperative cardiac complication with a positive predictive value of 0.857 and a negative predictive value of 0.978. Other factors related to cardiac complications by univariate analysis were a higher American Society of Anesthesiologists grade, a higher NYHA functional class and a history of hypertension. In multivariate analysis, however, high preoperative NT-proBNP level (>160 ng/L) only remained significant. CONCLUSION: An elevated preoperative NT-proBNP level is identified as an independent predictor of cardiac complications following lung resection surgery.